LANGUAGE SHIFTS IN JAVANESE NAMING SYSTEM: A CASE IN NGINCEP VILLAGE, YOGYAKARTA - SM, Syafrianto; Wardhani, Evi Murti; Istiqomah, Fitria Naimatul; Yanottama, Fourica (Leksema: Jurnal Bahasa dan Sastra, 2023)
The naming system for Javanese is an impressive tradition performing the Javanese culture and identity and has historically been the case in Javanese culture. The goal of this study is to identify and describe the name patterns of Ngincep citizens from 1900s to 2023, to investigate the cultural factors influencing the naming system of Ngincep residents, and to expose individual attention in the naming system as well as to map the language shifts. This research employed ethnographic and interactive models, each of which was implemented by participant observation and interviews. Additionally, sociolinguistic, ethnolinguistic, and onomastic approaches were also involved in this study. This study was located in Ngincep, a village in Bantul Regency, Yogyakarta Special Province. The data suggest that Javanese people's naming system in Ngincep was significantly affected by social classes, as discovered by Geertz, from the beginning of the 1900s to several decades later. However, the advancement of technology has recently changed this system, as evidenced by the number of words in names and the propensity of groups or individuals in naming children. The reason behind this phenomenon is also supposedly coming from the long-standing flexibility in the naming system for Javanese society, in general, and Yogyakarta Palace servant members, in particular, who are assigned as a part of their responsibilities to preserve Javanese culture and language, one of the cultural products.